2017
DOI: 10.1007/s11255-017-1644-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of tadalafil with sildenafil for the treatment of erectile dysfunction: a systematic review and meta-analysis

Abstract: AimsErectile dysfunction (ED) is a major care problem worldwide. Tadalafil and sildenafil are the two most common phosphodiesterase 5 inhibitors used to treat ED. This systematic review and meta-analysis were conducted to directly compare tadalafil with sildenafil for the treatment of ED.MethodsWe designed a strategy for searching the PubMed, Embase, EBSCO, Web of Science and Cochrane library databases; the reference lists of the retrieved studies were also investigated. A literature review was performed to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 40 publications
0
69
0
2
Order By: Relevance
“…Hypertension inhibits NO production by inhibiting the expression and phosphorylation of eNOS in corpus cavernosum tissue and finally results in ED (Li, Youn, & Cai, ). Phosphodiesterase 5 inhibitor (PDE5I), targeting the NO/cGMP signalling pathway, has become the first‐line drug for the treatment of ED including those caused by hypertension, with an effective rate of 60%–70% (Gong et al, ; Sommer & Engelmann, ). Some patients had poor results, and the erectile function could not be maintained in most patients after PDE5I withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension inhibits NO production by inhibiting the expression and phosphorylation of eNOS in corpus cavernosum tissue and finally results in ED (Li, Youn, & Cai, ). Phosphodiesterase 5 inhibitor (PDE5I), targeting the NO/cGMP signalling pathway, has become the first‐line drug for the treatment of ED including those caused by hypertension, with an effective rate of 60%–70% (Gong et al, ; Sommer & Engelmann, ). Some patients had poor results, and the erectile function could not be maintained in most patients after PDE5I withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Tadalafil significantly improved psychological outcomes. Furthermore, the patients and their partners preferred tadalafil over sildenafil, and no significant difference was found in the adherence and persistence rates between tadalafil and sildenafil (Gong et al, ). Despite sildenafil was the first in the PDE5 inhibitors family to offer a new approach in the field of treating ED, tadalafil seems to introduce new perspectives for the treatment and cure of ED.…”
Section: Resultsmentioning
confidence: 99%
“…NICE advice is that men with T2DM and ED should be offered "a PDE5 inhibitor with the lowest acquisition cost", which is sildenafil 25 mg and "4 tablets per month maximum" [3]. Multiple randomized controlled trials (RCTs) have shown that, at best 50% of patients succeed with "ondemand" PDE5 inhibitors even at the highest dose and with unrestricted medication [13]. The mechanism of ED in T2DM is predominantly endothelial dysfunction, a chronic pathology affecting the entire cardiovascular symptom, such that a single tablet of sildenafil with a half-life of 4 hours is unlikely to affect the underlying progressive pathological process.…”
Section: Current National Institute For Health and Care Excellence Amentioning
confidence: 99%
“…The multiple pathologies involved in ED in T2DM are outlined in Table 1. Effectively Roger was unlikely to achieve success [13].…”
Section: Current National Institute For Health and Care Excellence Amentioning
confidence: 99%